Facile Synthesis of Nitrogen‐Containing Mesoporous Carbon for High‐Performance Energy Storage Applications. Issue 12 (5th February 2016) - Xu, Yunling; Wang, Jie; Chang, Zhi; Ding, Bing; Wang, Ya; Shen, Laifa; Mi, Changhuan; Dou, Hui; Zhang, Xiaogang
Abstract: Porous carbon with high specific surface area (SSA), a reasonable pore size distribution, and modified surface chemistry is highly desirable for application in energy storage devices. Herein, we report the synthesis of nitrogen‐containing mesoporous carbon with high SSA (1390 m 2  g −1 ), a suitable pore size distribution (1.5–8.1 nm), and a nitrogen content of 4.7 wt % through a facile one‐step self‐assembly process. Owing to its unique physical characteristics and nitrogen doping, this material demonstrates great promise for application in both supercapacitors and encapsulating sulfur as a superior cathode material for lithium–sulfur batteries. When deployed as a supercapacitor electrode, it exhibited a high specific capacitance of 238.4 F g −1 at 1 A g −1 and an excellent rate capability (180 F g −1, 10 A g −1 ). Furthermore, when an NMC/S electrode was evaluated as the cathode material for lithium–sulfur batteries, it showed a high initial discharge capacity of 1143.6 mA h g −1 at 837.5 mA g −1 and an extraordinary cycling stability with 70.3 % capacity retention after 100 cycles. Abstract : Nitrogen‐doped mesoporous carbon : Nitrogen‐containing mesoporous carbon (NMC) with a highly developed mesopore structure has been prepared through a facile one‐step self‐assembly process. Electrochemical studies have demonstrated it to be a promising electrode material for high‐performance electrochemical double‐layer capacitors (EDLCs) and Li‐S batteries.